2008
DOI: 10.1016/j.jphotobiol.2008.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of summer daylight saving time on scattered erythemal solar ultraviolet exposures

Abstract: The research question of whether there are any influences in the scattered or diffuse erythemal UV exposures to a horizontal plane over a five month period due to the change from standard time to daylight saving time, has been investigated by using physical measurements and applying them to both standard time and daylight saving time. The diffuse erythemal UV was considered for fixed lunch break times and fixed morning and afternoon break times. The cases considered were for groups of the population who are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, little is known regarding the relative contribution of the direct, diffuse and reflected UV radiation to the anatomical exposure as individual dosimetric measurement cannot separate the three radiation components. Recent investigations of UV doses received by body parts unexposed to direct sunlight have suggested the importance of diffuse radiation 18,19 . UV irradiance measured in the shade (in Australia) during a short time‐period was sufficient to cause erythema and UV doses measured on the lower leg of cyclists showed that a potentially shaded anatomical site can receive half the dose of the maximally exposed sites 20 …”
mentioning
confidence: 99%
“…However, little is known regarding the relative contribution of the direct, diffuse and reflected UV radiation to the anatomical exposure as individual dosimetric measurement cannot separate the three radiation components. Recent investigations of UV doses received by body parts unexposed to direct sunlight have suggested the importance of diffuse radiation 18,19 . UV irradiance measured in the shade (in Australia) during a short time‐period was sufficient to cause erythema and UV doses measured on the lower leg of cyclists showed that a potentially shaded anatomical site can receive half the dose of the maximally exposed sites 20 …”
mentioning
confidence: 99%